Analisis Spasial Tingkat Kerawanan Hutan dan Lahan di Kabupaten Ngawi Berbasis Sistem Informasi Geografis - Burhanudddin Habibillah; Agus Anggoro Sigit; Dewi Novita Sari; Basyar Ihsan Arijuddin (Mataram University, 2026)
Forest and land fires represent a form of environmental disaster resulting from the interaction between natural factors and human activities in land use. Ngawi Regency, which is spatially dominated by agricultural and forested areas, exhibits biophysical and socio-environmental characteristics that may increase its vulnerability to forest and land fires. This study aims to assess the level of forest and land fire vulnerability in Ngawi Regency using a descriptive quantitative approach based on Geographic Information Systems (GIS). The analysis was conducted through scoring, spatial overlay, and vulnerability classification using the Equal Interval method applied to a set of biophysical and anthropogenic parameters. The results indicate that the study area is predominantly characterized by a moderate level of vulnerability, while areas with high and low vulnerability are more limited and spatially concentrated. The spatial pattern of vulnerability reveals a strong relationship between physical environmental conditions and the intensity of human activities. Areas located near settlements and road networks tend to exhibit higher vulnerability levels compared to areas with lower human influence. These findings highlight the importance of forest and land fire vulnerability mapping as a supporting tool for more targeted, adaptive, and sustainable mitigation planning aimed at reducing fire risk at the regional level.